The Role of Local Champion in Achieving an Integrated Rural Tourism: A Case Study of Alamendah Tourism Village, West Java - Rini Andari; Ahmad Hudaiby Galih Kusumah; Caria Ningsih (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2023)
Integrated rural tourism can provide welfare to the community and materialize the concept of sustainable tourism. The development carried out to achieve this requires synergy between the internal and external stakeholders. This study analyzes the role of local champions in achieving integrated rural tourism. This research uses a qualitative approach with a case study method to explore cases or phenomena that are interrelated to determine their uniqueness. The tourist village explored is Alamendah which has an ADWI (Anugerah Desa Wisata Indonesia) award 2021 from the government, the selection of this tourist village can be a guide for other tourist villages with a desire to grow. According to the findings of this study, the role of the chairman of the village, who is responsible for managing tourism in the village and acts as a local champion in establishing integrated rural tourism, is essential. Tourist villages also require leaders from their communities who can be trusted and influential in uniting their goals and mission.